1979
DOI: 10.1159/000122940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Castration on Serum Gonadotropin Levels in Androgenized Male and Female Rats

Abstract: The changes in LH and FSH secretion 12, 18 h and 1, 3, 5, 20 and 30 days following castration in adult rats of both sexes neonatally androgenized were studied. After castration, serum LH concentration rose slowly in the female and rapidly in male rats. Orchidectomy induced an increase of LH that was significantly slower in the androgenized rats than in the controls until 20 days after the postcastration period, reaching similar values at 30 days. In the female rats the increase in the LH levels from 48 h to 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Basal LH levels in neonatally androgenized females have been reported to be decreased (Korenbrot et al, 1975) or unchanged (Kubo et al, 1975) in the ovary-intact state. Following ovariectomy, LH levels rise at a significantly slower rate and remain chronically lower in neonatally androgenized females compared to their control counterparts (Moguilevsky et al, 1979). We have recently assessed the characteristics of LH pulsatility in long-term ovariectomized females that received neonatal testosterone or control treatments (Figure 9) (Foecking, unpublished).…”
Section: Neonatal Androgen Exposure: Effects On Basal Gonadotropin Sementioning
confidence: 99%
“…Basal LH levels in neonatally androgenized females have been reported to be decreased (Korenbrot et al, 1975) or unchanged (Kubo et al, 1975) in the ovary-intact state. Following ovariectomy, LH levels rise at a significantly slower rate and remain chronically lower in neonatally androgenized females compared to their control counterparts (Moguilevsky et al, 1979). We have recently assessed the characteristics of LH pulsatility in long-term ovariectomized females that received neonatal testosterone or control treatments (Figure 9) (Foecking, unpublished).…”
Section: Neonatal Androgen Exposure: Effects On Basal Gonadotropin Sementioning
confidence: 99%
“…'masculinize') the positive feedback effects of gonadal ste roids on gonadotropin secretion and induce, in adulthood, chronic anovulatory sterility and persistent estrus. Al though doses in the range of 1 mg of TP per rat are com monly used,a single injection of as little as 10 pg of TP ad ministered on or before postnatal day 4, will induce persis tent estrus in the majority of females [17], Previous studies of the effects of neonatal TP treatment on the postcastration LH rise in females have used high doses of TP (1.0-1.25 mg TP/rat), and found that the LH response was not 'masculinized' but, in fact, was even somewhat slower than in normal female controls [11,26,32], In the present study, we have found that this inhibitory effect of high-dose neonatal androgen treatment on the 'postcastration' LH response is not simply a result of altered sex steroid production in persistent estrous females. Fe males which were treated neonataliy with a high dose of TP (500 pg/rat), and then gonadectomized and implanted with T capsules for 3 weeks as adults, also showed a slower LH response following removal of the T capsule than did the similarly treated, oil-injected controls.…”
Section: Discussionmentioning
confidence: 99%
“…Females injected with the androgen, testosterone propionate (TP) during the 1st week of postnatal life exhibited serum LH responses to ovariectomy which were as slow or even slower than those shown by diestrous females [11,26,32]. However, in these studies, females were androgenized with doses of TP which were at least 100-fold greater than those required to block the cyclic release of gonadotropins [18].…”
mentioning
confidence: 99%